Exchange rates, foreign currency exposure and sovereign risk - Kerstin Bernoth; Helmut Herwartz (Journal of International Money and Finance, 2021)
We quantify the causal link between exchange rate movements and sovereign risk of 16 major emerging market economies (EMEs) by means of structural vector autoregressive models (SVARs) and conditional on data from 10/2004 through 12/2016. We apply a novel data-based identification approach of the structural shocks that allows to account for the complex interrelations within the triad of exchange rates, sovereign risks and interest rates. The direction and size of the response of sovereign risk to FX rate movements depend on the considered type of exchange rate measure and on the size of the net foreign currency exposure of an economy. A depreciation of the domestic currency against the USD increases sovereign risk. In contrast, when looking at the nominal effective exchange rate that is unrelated to changes of USD exchange rate, we find in general no significant effect. We conclude that the `financial channel' is more important in the transmission of exchange rate shocks to sovereign risk in comparison with the traditional `net trade channel'. Moreover, we confirm the prime role of the currency mismatch of the non-public sector for the strength of the `financial channel'.
Keywords: C32; G12; G15; G23; 330; Exchange rates; Sovereign risk; Foreign currency exposure; Structural VAR